The Role of Authentic Tasks in Developing Productive Skills (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The development of productive language skills—speaking and writing—is crucial for effective communication in any language. This study explores the role of authentic tasks in enhancing these skills among language learners. Authentic tasks, defined as tasks that mirror real-world language use, are posited to offer significant advantages over traditional, decontextualized exercises. This research employs a mixed-methods approach to evaluate the impact of authentic tasks on learners' speaking and writing proficiency. Quantitative data from proficiency tests and qualitative feedback from learners are analyzed to assess improvements in fluency, accuracy, and overall communicative competence. The findings suggest that authentic tasks significantly enhance productive skills by providing meaningful, context-rich opportunities for language use. This study contributes to the understanding of task-based language teaching (TBLT) and offers practical recommendations for integrating authentic tasks into language curricula.